INFORMATION SYSTEMS AUDIT CURRICULA CONTENT MATCHING - Vasile-Daniel CARDOȘ; Ildikó Réka CARDOȘ (SEA: Practical Application of Science, 2014)

(untitled)
Financial and internal auditors must cope with the challenge of performing their mission in technology enhanced environment. In this article we match the information technology description found in the International Federation of Accountants (IFAC) and the Institute of Internal Auditors (IIA) curricula against the Model Curriculum issued by the Information Systems Audit and Control Association (ISACA). By reviewing these three curricula, we matched the content in the ISACA Model Curriculum with the IFAC International Education Practice Statement 2 and the IIAs’ Global Model Internal Audit Curriculum. In the IFAC and IIA Curriculum there are 16 content elements, out of 19 possible, which match, in their description, the ISACA Model Curriculum’s content. We noticed that a candidate who graduates an IFAC or IIA compliant program acquire IS auditing competences similar to the specific content of the ISACA model curriculum but less than the requirements for a professional information systems auditor.